1981
DOI: 10.1111/j.1365-2184.1981.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation Inhibition of Murine Pluripotent Haemopoietic Stem Cells By Interferon Or Poly I:C

Abstract: The effect of mouse serum interferon (IF) in vitro and an inducer in vivo on the proliferation of a pluripotent stem cell population with high turnover rate was studied. Proliferation rate was characterized by the number of CFUs in the S phase of the cell cycle. Increased proliferation of bone marrow stem cell populations was produced either by irradiating the donor mice with 3·36 Gy (336 rad) 60Co‐gamma rays 7 days before the experiment or by incubating normal bone marrow cells with 10–11 M concentration of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The Mx1 - Cre system can be potentially associated with additional problems. For instance, pIpC administration has been suggested to trigger HSC cycling, similar to interferon itself ( Essers et al., 2009 , Gidali et al., 1981 , Sugiyama et al., 2006 ). While we found less evidence for a dramatic effect of pIpC in inducing HSPC proliferation, we noted that pIpC induced rapid and transient changes (that resolved by day 8) in cellular phenotypes, which could affect the interpretation of experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…The Mx1 - Cre system can be potentially associated with additional problems. For instance, pIpC administration has been suggested to trigger HSC cycling, similar to interferon itself ( Essers et al., 2009 , Gidali et al., 1981 , Sugiyama et al., 2006 ). While we found less evidence for a dramatic effect of pIpC in inducing HSPC proliferation, we noted that pIpC induced rapid and transient changes (that resolved by day 8) in cellular phenotypes, which could affect the interpretation of experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…pIpC reversibly inhibited expansion of primitive hematopoietic cells, probably reflecting a transient antiproliferative and/or apoptotic effect of interferon induced by pIpC treatment (Gidali et al, 1981). In addition, the numbers of CD34 2 c-kit + Sca-1 + Lin 2 and SP low cells were reduced in pIpC-treated wild-type and control MxCre-CXCR4 f/wt mice as well as MxCre-CXCR4 f/null mice at early time points after injection of pIpC (see Figure S1 in the Supplemental Data available online and data not shown).…”
Section: Induced Deletion Of Cxcr4 In Adult Bone Marrowmentioning
confidence: 98%
“…As in mice, loss of IFN signaling did not affect EMP numbers in zebrafish embryos [21], highlighting the specificity of IFNs on HSC and LP development. In addition, zebrafish morphants lacking IFN or its receptor had reduced expression of runx1, an important marker of HSPCs in the AGM region [27], thus supporting the significance of IFN in HSC emergence across species. Furthermore, Sawamiphak et al showed that IFN overexpression was sufficient to rescue loss of HSCs in two models (Notch signaling knockdown and blood loss) [27].…”
Section: Ifn Signaling During Developmental Hematopoiesismentioning
confidence: 75%
“…In addition, zebrafish morphants lacking IFN or its receptor had reduced expression of runx1, an important marker of HSPCs in the AGM region [27], thus supporting the significance of IFN in HSC emergence across species. Furthermore, Sawamiphak et al showed that IFN overexpression was sufficient to rescue loss of HSCs in two models (Notch signaling knockdown and blood loss) [27]. Similarly, zebrafish embryos lacking the IFN ortholog (IFNφ) had fewer HSPCs and thymocytes, whereas knockdown of Irf2a, a negative regulator of IFN signaling, had more of these cells.…”
Section: Ifn Signaling During Developmental Hematopoiesismentioning
confidence: 75%